Sucuiuba: justiça hídrica e ancestralidade na Chapada Diamantina - Oliveira, Cláudio Adão Dourado de (2024)
This work proposes a deep dive into five communities in the identity territory of Chapada Diamantina to analyze how each of them reacts and adapts to climate change, to maintain their engineering and water management systems in the face of growing water demand, the everincreasing need of irrigation to guarantee food production and the urgent appeal to environmental issues. These communities are located in areas of socio-environmental conflicts and with marked variations in water stress in recent years. Given this, the research is based on occurrences of conflicts between these communities and public water management in the last two years (2022/23) through participant observation, as a militant (ethnographic) researcher, followed by a semi-structured interview , based on interdisciplinary social research that values both the theoretical-political keys of Latin American critical thought – decolonial, southern epistemologies, ecofeminist and pluriversal – to the classics of historical-dialectic materialism. The idea is to connect these approaches, without attachment to structuralist formalisms, but attentive to the need to carry out empirical research in order to find a voice in the silence and produce new and useful knowledge to the daily challenges of the communities we work with. In general terms, this methodology combines the method of controlled equivocation with historical-dialectic materialism with an intellectual movement from the perspective of Living Sociology and Contra Anthropology. Based on the region's agrarian issues, I will wage an allegorical fight between the snake and the ox, the first of which represents peasant knowledge and diversity and the second of which represents the myth of national identity, represented by the State, with its global tendency to a standard model for decision-making and practical applicability of public water management, most often anchored in scientific rationality and knowledge control. In this way, I will demonstrate how this implemented model has been questioned both, for highlighting the Nation State as a political and legal reference, and for creating new logics of expulsions typical of global political economies, highlighting systems in crisis as pointed out by Porto Gonçalves (1989; 2001 ; 2002), Marshall Berman (2007) and Saskia Sassen (2014). This view suggests a more comprehensive panorama, where every form of knowledge is necessarily political, as it changes the modes and results of the distribution of ecological goods.